GLOBAL CLIMATE CHANGE AND ITS EFFECTS ON LIVING ORGANISMS - Sharipov Jasurbek Umidjon ugli; Toshturdiyev Nurbek Nurali ugli (Antis Publisher, 2024)
Global climate change, driven primarily by anthropogenic greenhouse gas emissions, represents a critical challenge with extensive implications for ecosystems and biodiversity. Rising global temperatures, altered precipitation patterns, and increased frequency of extreme weather events are influencing the habitat, distribution, and physiological processes of various organisms. Despite considerable research, there remains a limited understanding of how these climatic changes interact with other environmental stressors to affect different taxa and ecosystems. This study aims to elucidate the multifaceted impacts of climate change on living organisms by integrating data on physiological responses, species distributions, and ecological interactions. Our findings reveal that climate-induced shifts in temperature and precipitation significantly alter species distributions and community dynamics. Specifically, we observe accelerated phenological changes in some species, disrupted trophic interactions, and increased vulnerability of certain taxa to new stressors. This research advances the field by employing a multi-dimensional approach that combines ecological modeling with empirical data across various biomes, offering new insights into the interactive effects of climate variables on biological systems. The results underscore the urgency of incorporating climate change considerations into conservation strategies and policy-making to mitigate adverse impacts on biodiversity and ecosystem services. This study provides a critical foundation for developing adaptive management practices to enhance resilience in the face of ongoing climate shifts.